2022
DOI: 10.3390/plants11060807
|View full text |Cite
|
Sign up to set email alerts
|

Low Salt Treatment Results in Plant Growth Enhancement in Tomato Seedlings

Abstract: Climate change together with excessive fertilization and poor water quality can affect soil quality and salinization. In plants, high salinity causes osmotic stress, ionic toxicity, and oxidative stress. Consequently, salt stress limits plant development, growth, productivity, and yield. Tomatoes are a very common agricultural product, and some cultivars can partially tolerate salinity. However, most studies are focused on salt excess, which does not necessarily extrapolate on how plants develop in soils with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…These negative results can be attributed to the increase of salt concentration in the substrate, which negatively acts Table 1. Summary of F-test for number of leaves (NL), leaf area (LA), leaf fresh mass (LFM), bulb fresh mass (BFM), shoot fresh mass (SFM), bulb volume (BV), leaf dry mass (LDM), root dry mass (RDM), bulb dry mass (BDM), and total dry mass (TDM), specific leaf area (SLA), and leaf area ratio (LAR) of purple kohlrabi fertigated with nutrient solutions of different electrical conductivities (ECns) on the physiological process, reducing water absorption by roots, inhibiting meristematic activity, cell elongation, and consequently reducing plant growth and development (Chen et al, 2022;Ji et al, 2022;Rivera et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…These negative results can be attributed to the increase of salt concentration in the substrate, which negatively acts Table 1. Summary of F-test for number of leaves (NL), leaf area (LA), leaf fresh mass (LFM), bulb fresh mass (BFM), shoot fresh mass (SFM), bulb volume (BV), leaf dry mass (LDM), root dry mass (RDM), bulb dry mass (BDM), and total dry mass (TDM), specific leaf area (SLA), and leaf area ratio (LAR) of purple kohlrabi fertigated with nutrient solutions of different electrical conductivities (ECns) on the physiological process, reducing water absorption by roots, inhibiting meristematic activity, cell elongation, and consequently reducing plant growth and development (Chen et al, 2022;Ji et al, 2022;Rivera et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Even 1.5 g/L NaCl reduced the total fresh weight and dry weight of basil roots [35]. Plant height, stem diameter, leaf number, and dry mass of basil plants were significantly reduced when salt concentration was increased from 0 to 4.80 g/L NaCl [36]. In SETIS, the addition of 1 g/L NaCl seemed to be beneficial for shoot and root length, but at 3 g/L NaCl, there were already negative effects.…”
Section: Discussionmentioning
confidence: 96%
“…Another negative effect of salinity demonstrated in this experiment was the reduced chlorophyll content in both systems. The reduction of chlorophyll under salt stress has been demonstrated in basil [36], and in many other species, such as sugarcane [38], wheat and barley [39], tomato [40], Prosopis alba [41] and maize [42]. The reduction in chlorophyll content can be explained by the accumulation of intracellular Na + that blocks the uptake of K + from the medium.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in chlorophyll pigments in low (50 and 100 mM) NaCl doses suggests that the SC2121 variety was tolerant to low salt concentrations (Turfan, 2017;Çelik and Karakurt, 2022). However, the fact that the highest level was found in 50NaCl+250GLU, and 50NaCl-500GLU showed that the low level of glutamic acid application reduced the damage caused by salt stress (Sadak et al, 2015;Rivera et al, 2022). The parameter affected by the treatments the most was the ratio of chlorophyll a to chlorophyll b (Table 5).…”
Section: Effects Of Nacl and Glu Treatments On The Bioactive Chemical...mentioning
confidence: 99%